POE-Oriented Animated Video to Enhance Students’ Knowledge Competence in Flat Shapes Material for Fifth-grade Elementary School - Dewi, Kadek Desintia Putri Cahyani; Agustika, Gusti Ngurah Sastra; Sujana, I Wayan (Universitas Pendidikan Ganesha, 2025)
The low learning outcomes of students' mathematics, especially in flat building materials, are caused by traditional learning methods, limited interactive media, and lack of active participation of students in the learning process. This study aims to create animated video learning materials based on the Predict, Observe, Explain (POE) approach. This research uses the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model which was chosen because it is systematic and suitable to produce products in the form of POE-based animation learning media (Predict, Observe, Explain). The research subjects consisted of two groups, namely experts and students. The experts involved include learning media experts, learning design experts, and material experts who are in charge of assessing the feasibility of the product, while the field trial involved grade V students of SD Negeri 6 Sanur. The trial was carried out in stages ranging from individual tests, small group tests, to field tests with a total of 24 students. The data collection technique in this study uses several instruments, namely a closed questionnaire to assess product quality by experts and student response, multiple-choice tests (pre-test and post-test). The results showed a substantial improvement in student learning outcomes (tcount = 15.618> ttable = 1.714, p <0.05). The normal distribution was revealed from the results of the normality test of pre-test and post-test data (Xcount = 7.21 and 9.74 < Xtable = 11.07). This media has been shown to increase students' learning motivation while helping them understand the idea of the diameter and area of a flat building.